Giant cell tumor of patella - Paudel, S; Kayastha, P.; Pokharel, P; Shah, A; Ghimire, RK; Ansari, MA (Journal of Institute of Medicine Nepal, 2012)
Giant cell tumor of bone also known as osteoclastoma is a distinct clinical, roentgenographic and pathologic entity with specific characteristics. It is a benign but locally aggressive neoplasm of the epiphyseal or metaphyseal-epiphyseal region of long tubular bones extending to the articular surface. It usually occurs after skeletal maturation and is one of the rare bone tumors that more frequently affects women. We report here a case of giant cell tumor originating from the right patella diagnosed on fine needle aspiration cytology.